The Art of Public Speaking Missed by Generation Z - Sumiati, Imas (Unram Journal of Community Service, 2025)
Public speaking skills are still not fully possessed by students. This reluctance to appear in public is due to low self-confidence and a lack of public speaking skills. This inability causes what should be effective communication to become degraded. Even in public, communication misunderstandings often occur. This misunderstanding was documented and spread across the internet. As a service team, we took the initiative to conduct a public speaking activity at SMA 4 Pasundan Bandung. The Community Service activity aims to improve students' public speaking skills, enhance their ability to express ideas or opinions, boost their learning motivation, and increase their self-confidence. Public speaking skills are still not fully possessed by students. Therefore, by carrying out this service activity, we hope that the output from the students of SMA 4 Pasundan Bandung will be able to improve their good communication skills and increase their learning motivation and self-confidence, both in the classroom, within the school environment, outside the surrounding environment, and in their future work environment.